Physical cross-linking of starch hydrogel by short cycles of cooling and heating in the presence of glycerol for potential use as dermal dressing - Fornaizer, Mariana; Otaguro, Harumi (Eclética Química, 2026)
This study focused on developing films from physically cross-linked starch hydrogel with glycerol, utilizing short cooling and heating cycles to enhance cross-linking via the freeze-thaw process. Characterization revealed that 30% glycerol promoted physical cross-linking, further intensified by the thermal cycles, leading to increased film density (AG-R1, AG-R2, and AG-R4). The films demonstrated favorable physicochemical properties for reparative dressings, including easy handling, flexibility, high swelling capacity, water vapor permeability, and low solubility. Notably, the AG-R2 film exhibited the most significant changes, showing increased density and reduced thickness. This indicates a distinct morphology compared to the other films, suggesting an entanglement that restricts solvent molecules (water) incorporation during testing.